Direct Oxidation of Cyclopropanated Cyclooctanes as a Synthetic Approach to Polycyclic Cyclopropyl Ketones. Issue 7 (15th February 2018) - Sedenkova, Kseniya N.; Andriasov, Kristian S.; Stepanova, Svetlana A.; Gloriozov, Igor P.; Grishin, Yuri K.; Kuznetsova, Tamara S.; Averina, Elena B.
Abstract : A series of polycyclic hydrocarbons containing cyclopropane moieties 1, 2‐annelated or spiro‐condensed with a cyclooctane ring were investigated under oxidative conditions. Four oxidizing systems (O3 on SiO2, a dioxirane derived from trifluoroacetone, CrO3, and RuO4, generated in situ), were tested to evaluate and compare their reactivity and usefulness. RuO4 was found to be the best of them, considering its oxidative power together with the simple operating procedure. Conditions for the specific oxidation of polycyclic hydrocarbons were found. New cyclooctane derivatives containing cyclopropyl carbonyl moieties were obtained. Abstract : A comparison of different oxidizing systems as reagents for the direct oxygenation of cyclopropane‐containing hydrocarbons showed in‐situ generated RuO4 to be the most efficient and practical oxidant. Simple preparative procedures for the synthesis of polycyclic cyclopropyl ketones and diketones are presented.